Marketing Segmentation for Increasing Sales Volume in Islamic Economic Perspective - Widodo Saputro, Wahyu; Zulfikar Khatami; Salman Akbar (Islamicate Institute, 2023)
Market segmentation is a fundamental strategy in understanding the needs and preferences of diverse customers. This research uses qualitative methods with a literature study approach. The results of previous research and business practices confirm that market segmentation has a significant positive impact on a company's sales volume. First, segmentation allows companies to have a deep understanding of customer characteristics, needs, and preferences within each segment, leading to the development of more tailored products, services, and marketing messages. Secondly, through personalization of messages and marketing actions, segmentation increases the relevance of communication with customers, increases interest and likelihood of purchase. Furthermore, marketing segmentation helps companies to more efficiently allocate marketing resources, avoid waste, and direct efforts to the most relevant customer segments. Responsiveness to market changes is enhanced, allowing companies to quickly adjust their marketing strategies in the face of market changes. Overall, market segmentation is a crucial strategic tool in achieving increased sales volume in a competitive business environment. It helps companies better respond to customer needs, optimize resource usage, and create stronger relationships with customers, all factors that contribute to significant sales growth.